Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak: Studi Kasus Di Desa Talaga 2 - Muhammad Ilham; Febrina Rizki (Jurnal Sultra Elementary School, 2022)
This study aims to determine the parenting styles used by parents in shaping children’s discipline character in Talaga Village. This research is a qualitative study with a descriptive approach. Data collection techniques included observation, interviews, and documentation, which were then analyzed through data reduction, data presentation, and conclusion drawing. The validity of the data was verified using source triangulation, technique triangulation, and time triangulation. The results showed that parents in Talaga Village applied several parenting styles: the authoritarian style was used when parents enforced strict discipline; the permissive style appeared when parents were preoccupied with work; and the democratic style was used when parents and children created and agreed upon rules together, with corresponding consequences for violations. The discipline character developed among children included religious discipline (performing prayers regularly), time discipline (being punctual for prayers, waking up early, and returning home on time), and social discipline (showing respect to parents). The democratic parenting style was the most dominant, although in certain situations, parents also applied authoritarian and permissive styles. Factors influencing parenting practices included parents’ busy schedules, peer influence, economic status, and the negative effects of globalization such as the use of mobile phones, television, and online games.